Carrier-Tumor Cell Membrane Interactions for Optimized Delivery of a Promising Drug, 4(RS)-4-F4t-Neuroprostane - Ariana Abawi; Céline Thomann; Giovanna Lollo; Thierry Granjon; Emma Petiot; Anna Bérot; Camille Oger; Valérie Bultel-Poncé; Alexandre Guy; Jean-Marie Galano; Thierry Durand; Agnès Girard-Egrot; et al. (MDPI AG, 2023)
Nanomedicines engineered to deliver molecules with therapeutic potentials, overcoming drawbacks such as poor solubility, toxicity or a short half-life, are targeted towards their cellular destination either passively or through various elements of cell membranes. The differences in the physicochemical properties of the cell membrane between tumor and nontumor cells have been reported, but they are not systematically used for drug delivery purposes. Thus, in this study, a new approach based on a match between the liposome compositions, i.e., membrane fluidity, to selectively interact with the targeted cell membrane was used. Lipid-based carriers of two different fluidities were designed and used to deliver 4(RS)-4-F4t-Neuroprostane (F4t-NeuroP), a potential antitumor molecule derived from docosahexaenoic acid (DHA). Based on its hydrophobic character, F4t-NeuroP was added to the lipid mixture prior to liposome formation, a protocol that yielded over 80% encapsulation efficiency in both rigid and fluid liposomes. The presence of the active molecule did not modify the liposome size but increased the liposome negative charge and the liposome membrane fluidity, which suggested that the active molecule was accommodated in the lipid membrane. F4t-NeuroP integration in liposomes with a fluid character allowed for the selective targeting of the metastatic prostate cell line PC-3 vs. fibroblast controls. A significant decrease in viability (40%) was observed for the PC-3 cancer line in the presence of F4t-NeuroP fluid liposomes, whereas rigid F4t-NeuroP liposomes did not alter the PC-3 cell viability. These findings demonstrate that liposomes encapsulating F4t-NeuroP or other related molecules may be an interesting model of drug carriers based on membrane fluidity.